Comparing KHI and KHES in Marital Property Grant Disputes: An Analysis of Judges' Views - Apriantoro, Muhamad Subhi; Alis, M. Naufal Ibnu; Septianozakia, Sendy; Setiana, Dadang (Institut Agama Islam Negeri Curup, 2023)
This study aims to assess how judges make decisions regarding disputes over grants on marital property from the perspectives of two legal systems, KHI and KHES. Specifically, the study examines a case (numbered 145/Pdt.G/2021/PA.Slk) that was heard at the Solok City, West Sumatera Religious Court and involved a communal property grant dispute. The research methodology used was normative juridical, a quantitative approach that uses secondary legal principles, and a qualitative system that relies on library research data. The study's findings indicate that comparing grant arrangements by Compilation of Islamic Law and Compilation of Sharia Economic Law, specifically in terms of the pillars mentioned in KHI and KHES, is closer to the consensus of scholars but not identical because KHI has additional witnesses and KHES has qabd.